2014
DOI: 10.1016/j.pec.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Women's preferences for selective estrogen reuptake modulators: An investigation using protection motivation theory

Abstract: Health professionals need to explore women's perceptions of their risk and its consequences, as well as providing clear evidence-based information about the efficacy of SERMs. Exploring the source and strength of beliefs about SERMs may allow more effective, tailored counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Only 15% of BRCA mutation carriers approached for a chemoprevention trial enrolled [2], and only 8.5% of BRCA mutation carriers offered chemoprevention started such a regimen within 4 years of receiving genetic test results [77]. These usage rates fall far short of the proportion of women interested in chemoprevention, which one study found to be upwards of 40% [93] of those with familial risk. Chemoprevention also poses the challenge of long-term adherence: a large study of women at familial risk found that almost half of those who started tamoxifen chemoprevention did not complete the 5-year regimen [59, 94].…”
Section: Women’s Prevention Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 15% of BRCA mutation carriers approached for a chemoprevention trial enrolled [2], and only 8.5% of BRCA mutation carriers offered chemoprevention started such a regimen within 4 years of receiving genetic test results [77]. These usage rates fall far short of the proportion of women interested in chemoprevention, which one study found to be upwards of 40% [93] of those with familial risk. Chemoprevention also poses the challenge of long-term adherence: a large study of women at familial risk found that almost half of those who started tamoxifen chemoprevention did not complete the 5-year regimen [59, 94].…”
Section: Women’s Prevention Choicesmentioning
confidence: 99%
“…Chemoprevention also poses the challenge of long-term adherence: a large study of women at familial risk found that almost half of those who started tamoxifen chemoprevention did not complete the 5-year regimen [59, 94]. Additional studies are needed to fully understand the barriers to chemoprevention use, but they include: research gaps (limited risk prediction at the individual level and questions about risk-benefit profiles for specific subgroups); physician challenges (insufficient knowledge, difficulty identifying chemoprevention candidates, lack of training and confidence in risk assessment and counseling, and lack of time); and patient challenges (fear of side effects, predicted stress associated with chemoprevention, inaccurate or incomplete information, weighing witnessed experiences more heavily than statistical probabilities, and concerns about insurance coverage or cost) [3, 93101]. It is important to understand low uptake better and to address the associated challenges, particularly in light of the recent review panel estimate that up to 50% of breast cancers among women at elevated risk could be prevented using currently available chemoprevention [56].…”
Section: Women’s Prevention Choicesmentioning
confidence: 99%
“…In order to aid the development of future interventions, future studies ought to include a theoretical framework to understand health decisions in addition to validated measures to assess psychological constructs that may influence decisions. One study [48] has considered Protection Motivation Theory to predict intentions to have CPM using a hypothetical scenario after previous research has demonstrated its utility in predicting intentions for genetic testing [49] and chemoprevention [49] for breast cancer.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The protection motivation theory (PMT) was originally developed in 1975 by Ronald Rogers to describe the process behind the attitudinal and behavioral changes that people undertake when faced with a real or perceived threat to their health ( 26 ). To the best of our knowledge, there has been previously no study to sufficiently probe into the effects of MI on overweight and obesity based on the PMT in Iran.…”
Section: Introductionmentioning
confidence: 99%